A Positive Side to Apophaticism: Prolegomena - Gilski, Marek (Verbum Vitae, 2023)
The article synthetically presents positive aspects of apophaticism. It discusses its apologetic role, its importance in defending against magical thinking, its focus on experience, its openness to pluralism, and its inspirational role for a variety of disciplines in delimiting their cognitive boundaries. Some of the most important conclusions are: a) apophaticism played an important role in the early days of Christianity in polemics against both pagan cults and magical tendencies; b) already in ancient Greece apophaticism influenced the search not only for symbolic interpretations of Homer’s poems but also for religious experience; c) the limits of cognition discovered by theology are becoming a contemporary experience of other sciences (mathematics, physics).